Reaching to Sounds Improves Spatial Hearing in Bilateral Cochlear Implant Users. Issue 1 (19th August 2022) - Valzolgher, Chiara; Gatel, Julie; Bouzaid, Sabrina; Grenouillet, Solene; Todeschini, Michela; Verdelet, Gregoire; Salemme, Romeo; Gaveau, Valerie; Truy, Eric; Farnè, Alessandro; Pavani, Francesco
Abstract : Objectives: We assessed if spatial hearing training improves sound localization in bilateral cochlear implant (BCI) users and whether its benefits can generalize to untrained sound localization tasks. Design: In 20 BCI users, we assessed the effects of two training procedures (spatial versus nonspatial control training) on two different tasks performed before and after training (head-pointing to sound and audiovisual attention orienting). In the spatial training, participants identified sound position by reaching toward the sound sources with their hand. In the nonspatial training, comparable reaching movements served to identify sound amplitude modulations. A crossover randomized design allowed comparison of training procedures within the same participants. Spontaneous head movements while listening to the sounds were allowed and tracked to correlate them with localization performance. Results: During spatial training, BCI users reduced their sound localization errors in azimuth and adapted their spontaneous head movements as a function of sound eccentricity. These effects generalized to the head-pointing sound localization task, as revealed by greater reduction of sound localization error in azimuth and more accurate first head-orienting response, as compared to the control nonspatial training. BCI users benefited from auditory spatial cues for orienting visual attention, but the spatial training did not enhance this multisensory attention ability. Conclusions: Sound localization in BCI users improves with spatial reaching-to-sound training, with benefits to a nontrained sound localization task. These findings pave the way to novel rehabilitation procedures in clinical contexts.